Performance evaluation of Barley (Hordeum vulgare L.) genotypes in Dolakha, Nepal: from yielding perspective - Kandel, Manoj; Dhami, Narayan Bahadur; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2019)
Lack of suitable barley varieties that exhibit high yielding is the major factor among several production constraints contributing to low productivity of barley in Nepal. The present study was done to evaluate and recommend the best performing barley genotypes. This study was conducted at research field of Hill Crops Research Program (HCRP), Dolakha, Nepal under National observation nursery (NON), initial evaluation trial (IET), coordinated varietal trials (CVT) and farmer's field trials (FFT) during winter seasons from 2017 to 2018. The results of these trials showed that in NON, genotypes namely B86023-1K2-OK3 (6.16 t/ha), Xveola-28/MATICO"S"10 (4.41 t/ha) and ACC#2079 (4.41 t/ha) produced higher grain yield over Farmer’s variety (3.57 t/ha). The pooled analysis over years of IET revealed that genotypes namely LG-51/Xveola-2-77-0-3-1-1-OK (2.12 t/ha) and B86099-2-1-OK (2.06t/ha) produced higher grain yield over standard check variety (Solu Uwa) (1.85 t/ha) and Farmer’s variety (1.95 t/ha). Similarly results of combined analysis over years of CVT showed that the genotypes namely B90K-007-0-2-2-0-OK (2.14 t/ha) and ICB90-0196-OAP-2K-OK (1.97 t/ha) produced higher grain yield over standard check variety (Solu Uwa) (1.12 t/ha) and Farmer’s variety (1.66 t/ha). In farmer's field trials (FFTs) the genotypes namely Muktinath ( Coll#112-14 (2.64 t/ha)), NB-1003-37/903 (2.23 t/ha) and Xveola-45 (2.04 t/ha) produced higher grain yield which was at par to standard check variety (Soluuwa) (1.58 t/ha) and Farmer’s variety (1.85 kg/ha). It is suggested that the superior genotypes derived from CFFT could be released and then recommended to farmers for general cultivation in Dolakha and similar other environments of Nepal.